Weapons barrel life cycle determination - Hristov, Nebojša Pene; Jovičić, Gordana R. (Vojnotehnički glasnik / Military Technical Courier, 2013)
This article describes the dynamic processes within the gun barrel during the firing process in exploitation. It generally defines the basic principles of constructing tube elements, and shows the distortion of the basic geometry of the tube interior due to wear as well as the impact it causes during exploitation. The article also defines basic empirical models as well as a model based on fracture mechanics for the calculation of a use-life of the barrel, and other elements essential for the safe use of the barrel as the basic weapon element. Erosion causes are analysed in order to control and reduce wear and prolong the lifetime of the gun barrel. It gives directions for the reparation of barrels with wasted resources. In conclusion, the most influential elements of tube wear are given as well as possible modifications of existing systems, primarily propellant charges, with a purpose of prolonging lifetime of gun barrels. The guidelines for a proper determination of the lifetime based on the barrel condition assessment are given as well. INTRODUCTION The barrel as the basic element of each weapon is described as well as the processes occurring during the firing that have impulsive character and are accompanied by large amounts of energy. The basic elements of barrel and itheir constructive characteristics are descibed. The relation between Internal ballistics, ie calculation of the propellant gas pressure in the firing process, and structural elements defined by the barrel material resistance is shown. In general, this part of the study explains the methodology of the gun barrel structural elements calculation, ie. barrel geometry, taking into account the degrees of safety in accordance with Military Standards. TUBE WEAR AND DEFORMATIONS The weapon barrel gradually wears out during exploitation due to which it no longer satisfies the set requirements. It is considered that the barrel has experienced a lifetime when it fails to fulfill the most important requirements of Military Standards (muzzle velocity, caliber size and shooting accuracy). In studies of barrel wear, there are numerous theories that explain barrel wear as thermal, mechanical and chemical effects of the projectile and propellant gas on the inner tube surface. It was found that barrel wear is a result of simultaneous effects of all factors mutually linked and very complex, so that, theoretically speaking, they cannot be uniformly determined. The extent of effects of particular factors in the wear process depends on the type of weapon systems and exploitation conditions (mode of fire, intensity and mode of barrel cooling, maintenance, storage conditions, etc.). It is considered that, for small arms, the main factor of wear is the effect of projectiles on the barrel while for artillery weapon barrels it is the erosive effect of powder gases. A life-death barrel which is determined by "ballistic death," is not necessary to be discarded, ie reparation can be done by "new calibration". The procedure of barrel reparation is economically acceptable and gives the possibility of extension of working lifetime and modification of the gun barrel. METHODS OF BARREL LIFE-TIME CALCULATION The conditions for calculating the gun barrel lifetime are described. Since the barrel lifetime depends primarily on the exploitation regime, the usage procedure (shooting program in the military terminology) Is prescribed for each individual weapon in particular. The lifetime empirical calculation methods discussed here comprise the methods of French and Russian scientists, i.e.Justrov, Linte, Gabo and Orlov. They are mainly based on empirical constants and elements of the barrel, bullet, projectile velocity and mode of fire. These methods are only partially reliable and cannot predict with certainty the barrel lifetime, - for example, some expressions state that lifetime increases with the increase in initial velocity and barrel caliber, which is incorrect and contrary to the results of the exploitation in practice. As far as modern methods are concerned, the principles of fracture mechanics according to the Paris expression and the modified expression of Smith-O’Braski are discussed. A reference value is the crack dimensions, i.e. material fatigue, and, due to the regime of exploitation, temperature, material, pressure, etc. are also taken into account. For the purpose of controlled wear and extension of the barrel lifetime, the following means for wear reduction are used: agents for lowering the tube surface temperature; so-called "cold" gunpowders; less erosive propellant charges; reduction of the leading ring stress using so-called "inert" materials which provide the necessary rotation of projectiles and reliable sealing of propellant gases along the tube and the use of improved types of barrel materials or the use of coatings and layers (liners) resistant to three main causes of erosion. The application of these barrel materials significantly increases the barrel lifetime (Tables 2 and 3). CONCLUSION The problem of tube wear and the definition of a method for predicting tube lifetime is very complex and multidisciplinary. This problem requires a team work of experts that would cover the following fields: mechanics of weapons, internal and external ballistics, fluid mechanics, thermodynamics, strength of materials, fracture mechanics, metallurgy, physical chemistry, maintenance and diagnostics. Since diagnostics, i.e. the determination of the tube technical conditions, precedes a prognosis of the tube service lifetime, it is logical that the first step towards solving this complex problem is to estimate the conditions, which should serve as a good basis for a proper evaluation of the tube lifetime.